ANALISIS PROBLEMATIK SURAT EDARAN BUPATI TULUNGAGUNG TERKAIT PENGATURAN PENANGGULANGAN CORONA VIRUS DISEASE 2019: (COVID-19) - Kuncoro, Adi; Widodo, Hananto (NOVUM : JURNAL HUKUM, 2018)
Handling Covid-19 which must be completed immediately must be made a special treatment. The urgent situation requires that a binding regulation be made in the situation of handling Covid-19 very quickly. The Tulungagung Regency Government issued a Circular regarding the implementation of Large-Scale Social Restrictions (PSBB). The problem is that the Circular which is a policy regulation can only regulate it, not for the wider community. This study aims to determine the function of the Circular issued by the regent as discretion in handling Covid-19 by regulating the community curfew, and to find out the legal consequences of issuing a circular letter by the regent in handling Covid-19. The research method used is a normative juridical type, using a statutory approach and a concept approach. The results of the study show that the Circular issued is categorized as a beleidsregel (policy regulation). This circular has the same legal status as operational guidelines, technical guidelines, official notes, announcements, guidelines and other similar terms. Beleidsregel is similar to regeling, but it is not intended/binding in general to the community and only binds internally to an institution. So that the regulation related to PSBB in the Tulungagung area related to the implementation of the curfew for all large business actors and MSMEs is less productive. The Circular issued by the Regional Government of Tulungagung Regency can be considered as a discretion. This is because there should be another mechanism established to be able to regulate the establishment of a Regional Regulation.